Effect of cutting and storage temperature on Packham’s Triumph pears (Pyrus communis L.) (2018)
For the minimally processed (MP) fruit, the cutting type and temperature are the main factors in order to maintain good quality and appearance. The objective of this work was to evaluate the effects of cutting type and storage on the metabolic activity, color, firmness, aroma profile and, organic acid and sugar content of MP pears (Pyrus communis L. cv. Packham’s Triumph). Whole fruits were washed, peeled and cut in wedges or dice. Then, the pieces were packaged in plastic containers and stored 8 days at 5 or 8 ºC. The cutting type and storage temperature had an important effect on the physiological parameters, color, firmness and organic acid and sugar content. However, the aroma volatile content was reduced independently of the cutting type and the storage temperature. Therefore, the pear cultivar Packham’s Triumph should be cut in wedges and stored 8 d at 5º C to maintain an optimum global quality.